Entrepreneurship, Agglomeration and Technological Change - Zoltán J. Ács; Attila Varga (Max Planck Institute for Research into Economic Systems, 2004)
Technological change is a central element in macroeconomic growth explanation. Endogenous growth models take a revolutionary step towards better understanding the economic growth process by deriving technological change from profit-motivated individual behavior. In endogenous growth theory knowledge spillovers play a fundamental role in the determination of the rate of technological progress. As such the efficiency of transmitting knowledge into economic applications is a crucial factor in explaining macroeconomic growth. Endogenous growth models take this factor exogenous. We argue that variations across countries in entrepreneurship and the spatial structure of economic activities could potentially be the source of different efficiencies in knowledge spillovers and ultimately in economic growth. We develop an empirical model to test both the entrepreneurship and the geography effects on knowledge spillovers. To date the only international data that are collected on the basis of exactly the same principles in each country are the Global Entrepreneurship Monitor (GEM) data. We use the 2001 GEM cross-country data to measure the level of entrepreneurship in each particular economy. For this purpose we apply the TEA index developed within the framework of the GEM project and calculated for each country participating in this international research. Additionally, data on employment, production, patent applications, public and private R&D expenditures originating from different international and national sources are applied in the paper.
Keywords: 330; Unternehmer; Regionale Konzentration; Wirtschaftsgeographie; Wissenstransfer; Technischer Fortschritt; Theorie